Synthesis, Double-Helix Formation, and Higher-Assembly Formation of Chiral Polycyclic Aromatic Compounds: Conceptual Development of Polyketide Aldol Synthesis - Yamaguchi, Masahiko; Shigeno, Masanori; Saito, Nozomi; Yamamoto, Koji (Chemical record, 2014)
Polycyclic aromatic compounds are an important group of substances in chemistry, and the study of their properties is a subject of interest in the development of drugs and materials. We have been conducting studies to develop chiral polycyclic aromatic compounds, i.e., helicenes and equatorenes. These helical molecules showed notable aggregate‐forming properties and the capability for chiral recognition exerted by noncovalent bond interactions, which were not observed in compounds with central chirality. Homo‐ and hetero‐double‐helix‐forming helicene oligomers were developed, and the latter self‐assembled to form gels and vesicles. In this article, we describe such hierarchical studies of polycyclic aromatic compounds, which were started from polyketide aldol synthesis. Polycyclic aromatic compounds are a group of important substances in chemistry, and the study of their properties is a subject of interest in the development of drugs and materials. We have been conducting studies to develop chiral polycyclic aromatic compounds, i.e., helicenes and equatorenes. These helical molecules showed notable aggregate‐forming properties and the capability for chiral recognition exerted by noncovalent bond interactions, which were not observed in compounds with central chirality. Homo‐ and hetero‐double‐helix‐forming helicene oligomers were developed, and the latter self‐assembled to form gels and vesicles. In this article, we describe such hierarchical studies of polycyclic aromatic compounds, which were started from polyketide aldol synthesis.